Duplex–quadruplex motifs in a peculiar structural organization cooperatively contribute to thrombin binding of a DNA aptamer. (1st December 2013) - Russo Krauss, Irene; Pica, Andrea; Merlino, Antonello; Mazzarella, Lelio; Sica, Filomena
<x xml:space="preserve">Abstract</x> Potent second‐generation thrombin aptamers adopt a duplex–quadruplex bimodular folding and recognize thrombin exosite II with very high affinity and specificity. A sound model of these oligonucleotides, either free or in complex with thrombin, is not yet available. Here, a structural study of one of these aptamers, HD22‐27mer, is presented. The crystal structure of this aptamer in complex with thrombin displays a novel architecture in which the helical stem is enchained to a pseudo‐G‐quadruplex. The results also underline the role of the residues that join the duplex and quadruplex motifs and control their recruitment in thrombin binding.